THE ROLE OF ACCESS TO INFORMATION IN ENSURING HUMAN RIGHTS (TSUL LEGAL REPORT, 2026)
This article provides a brief analysis of legislation on the role of obtaining information in ensuring human rights. The constitutional right to information is one of the basic rights of a person, and at the same time, it works as an external expression of freedom of opinion and freedom of speech, as well as their guarantee. The right to receive information, naturally, based on the characteristics of the information society, occupies a leading position in the state management mechanism. This is a special guarantee of the implementation of the principles of democracy, people’s sovereignty, and citizens’ participation in political life.